2018
DOI: 10.1038/s41598-018-23794-5
|View full text |Cite
|
Sign up to set email alerts
|

Foxn1 expression in keratinocytes is stimulated by hypoxia: further evidence of its role in skin wound healing

Abstract: Recent studies have shown that the transcription factor Foxn1, which is expressed in keratinocytes, is involved in the skin wound healing process, yet how Foxn1 functions remains largely unknown. Our latest data indicate that Foxn1 drives skin healing via engagement in re-epithelization and the epithelial-mesenchymal transition (EMT) process. In the present study, 2D-DIGE proteomic profiling analysis of in vitro cultured keratinocytes transfected with adenoviral vector carrying Foxn1-GFP or GFP alone (control)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
47
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(64 citation statements)
references
References 53 publications
8
47
0
9
Order By: Relevance
“…Mori, Itoi, Tsukamoto, & Amagai, 2010). In the skin, where Foxn1 is expressed in the epidermis and in hair follicles, it participates in hair follicle development, promotes keratinocyte differentiation and participates in the pigmentation process (Kur-Piotrowska et al, 2018;Lee, Prowse, & Brissette, 1999;Li et al, 2007;Weiner et al, 2007). Loss-of-function mutations in the Foxn1 gene has pleiotropic effects, similar in humans and mice and result in a lack of hair and the absence of the thymus and T cells (Brissette, Li, Kamimura, Lee, & Dotto, 1996;Frank et al, 1999;Nehls, Pfeifer, Schorpp, Hedrich, & Boehm, 1994;Pignata et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mori, Itoi, Tsukamoto, & Amagai, 2010). In the skin, where Foxn1 is expressed in the epidermis and in hair follicles, it participates in hair follicle development, promotes keratinocyte differentiation and participates in the pigmentation process (Kur-Piotrowska et al, 2018;Lee, Prowse, & Brissette, 1999;Li et al, 2007;Weiner et al, 2007). Loss-of-function mutations in the Foxn1 gene has pleiotropic effects, similar in humans and mice and result in a lack of hair and the absence of the thymus and T cells (Brissette, Li, Kamimura, Lee, & Dotto, 1996;Frank et al, 1999;Nehls, Pfeifer, Schorpp, Hedrich, & Boehm, 1994;Pignata et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Under hypoxic conditions, Hif-1α is protected from degradation due to depletion of PHDs and Fih-1 via proteasomal degradation and enhancement of the Hif-1α protein levels by thioredoxin (Trx-1) (Karlenius & Tonissen, 2010;Kur-Piotrowska et al, 2018;Zhou, Damdimopoulos, Spyrou, & Brune, 2007). Then, Hif-1α translocates to the nucleus, undergoes dimerization with Hif-1β and activates the transcription of downstream genes, e.g., vascular endothelial growth factor (VEGF), platelet-derived growth factor B-chain (PDGF-B) and heat shock protein (HSP-90) (L. Chen, Gajendrareddy, & DiPietro, 2012;Lokmic et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Communication between the epidermis and underlying dermis is necessary for tissue homeostasis and involves the secretion of multiple factors 16 . We previously showed that the profiles of synthesized transcripts (e.g., Wnt10a, Wnt11, and β-catenin) and proteins that may be implicated in the molecular cross-layer dialogue differ between Foxn1deficient (nude) and Foxn1-active (wild-type control) mice 17,18 . Foxn1 transcription factor deficiency corresponds with the unique ability of mammalian skin to regenerate when injury occurs [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…The re‐epithelialization process includes three stages of epidermal cell proliferation, migration and differentiation in which the migration of epidermal cells is the key step of re‐epithelialization on the wound surface . After acute wound formation, due to the disorder of the local blood circulation, the oxygen supply is reduced; meanwhile, the metabolism of the wound cells is active and proliferation increases, which leads to an increase in oxygen consumption, which results in the formation of an acute hypoxic microenvironment . Related studies have shown that acute hypoxia of the wound promotes wound healing by promoting the proliferation and migration of epidermal cells, fibroblasts and vascular endothelial cells, but the specific molecular mechanism is unclear.…”
Section: Introductionmentioning
confidence: 99%